The ileal fungal microbiota is altered in Crohn's disease and is associated with the disease course - Olaisen, Maya; Richard, Mathias L.; Beisvåg, Vidar; Granlund, Atle van Beelen; Røyset, Elin S.; Rué, Olivier; Martinsen, Tom Christian; Sandvik, Arne Kristian; Sokol, Harry; Fossmark, Reidar (Frontiers in Medicine, 2022)
Introduction: Fungal microbiota’s involvement in the pathogenesis of Crohn’s disease (CD) is incompletely understood. The terminal ileum is a predilection site both for primary involvement and recurrences of CD. We therefore assessed the mucosa-associated mycobiota in the inflamed and non-inflamed ileum in patients with CD. Methods: The mucosa-associated mycobiota was assessed by ITS2 sequencing in a total of 168 biopsies sampled 5 and 15 cm proximal of the ileocecal valve or ileocolic anastomosis in 44 CD patients and 40 healthy controls (HC). CD patients with terminal ileitis, with endoscopic inflammation at 5 cm and normal mucosa at 15 cm and no history of upper CD involvement, were analysed separately. The need for additional CD treatment the year following biopsy collection was recorded. Results: CD patients had reduced mycobiota evenness, increased Basidiomycota/Ascomycota ratio and reduced abundance of Chytridiomycota compared to HC. The mycobiota of CD patients were characterised by an expansion of Malassezia and a depletion of Saccharomyces, along with increased abundances of Candida albicans and Malassezia restricta. Malassezia was associated with need for additional anti-inflammatory treatment during follow-up. Current anti-TNF treatment was associated with lower abundances of Basidiomycota. The alpha diversity of the inflamed and proximal non-inflamed mucosa within the same patients was similar. However, the inflamed mucosa had a more dysbiotic composition with increased abundances of Candida sake and reduced abundances of Exophiala equina and Debaryomyces hansenii. Conclusions: The ileal mucosa-associated mycobiota in CD patients is altered compared to HC. The mycobiota in the inflamed and proximal non-inflamed ileum within the same patients harbour structural differences which may play a role in the CD pathogenesis. Increased abundance of Malassezia was associated with an unfavourable disease course.